Tingkah Laku Menetas Piyik Burung Weris (Gallirallus philipensis) dan Burung Dewasa dalam Penangkaran (HATCHING BEHAVIOR AND BEHAVIOR IN CAPTIVITY OF GALLIRALLUS PHILIPPENSIS) - Lambey, Lucia Johana; Noor, Ronny Rachman; Manalu, Wasmen; Duryadi, Dedy (Jurnal Veteriner, 2015)
The study of behavior has a very important role in wildlife management process both for cultivationand for preservation in nature. The purpose of this study was to observe and document behaviors and dailyactivities of weris. Observation of hatching process and behavior of juvenile weris used direct observationmethod, while the behavior of adult weris in captivity used scanning sampling method. The data wereanalyzed descriptively. Weris had six stages of hatching processes starting from the breakdown of the eggshell until the chick moved out from the shell. The placement of the eggs in hatching machine was byputting the dull part on upside. Weris is a diurnal bird that active in the morning until late afternoon.Young and adult weris birds had different activities, i.e., adult birds did bathing and flying activities,while the young birds just rest and sleep. Observation on behavior of adult weris (n = 10) showed that thehighest activity for 12 hours was moving (314,6 minutes), then followed by resting (283,1 minutes), eating(51,8 minutes), drinking (29 minutes), bathing (22,9 minutes), and the lowest was preening (18,6 minutes).Inherited behavior pattern, such as bathing, did not change, eventhough the environment changed.
Keywords: behavior, weris bird, Gallirallus philippensis